THE EFFECTIVENESS OF INTERACTION BETWEEN TEACHERS AND STUDENTS THROUGH ZOOM MEETING FOR HIGH SCHOOL - Alimah, Annisa Nur; Amalia Ghaitsa, Shera; Wahyunengsih, Wahyunengsih (Journal of Innovation Research and Knowledge, 2022)
The surge in the Covid-19 virus has forced everyone to minimize gatherings in close proximity, including school children. So, distance learning is held through many applications, for example, the Zoom virtual world meeting application. By utilizing today's technology, it is not impossible to do learning like in school. This study aims to see if the interaction between teachers and students through the Zoom application is as effective as face-to-face learning. This study used a linear method questionnaire with a scale of one to four to collect data. The target population of our research is high school students in grade 10 who carry out teaching and learning activities via Zoom. We will distribute questionnaires to thirty grade 10 students online as a sample for our research. The thirty students will be asked to fill out a questionnaire consisting of sixteen questions on a scale from one to four, depending on their personal experience. This study uses a qualitative type to produce more comprehensive and clearly describes the effectiveness of interactions between teachers and students through Zoom virtual meetings. Based on the results of the questionnaire, the students felt the most relevant to question number 4 which touched the figure of 71.1%. Based on the results of the study, it can be concluded that distance learning using the Zoom media is indeed suitable if it is carried out when the Covid-19 situation is soaring. However, if the situation is starting to be safe as it is now, it is better to study and discuss offline because it is much more effective if teachers and students can interact face-to-face.